2010
DOI: 10.1002/ajh.21735
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of characteristics from White‐ and Black‐Americans with venous thromboembolism: A cross‐sectional study

Abstract: When compared with Whites, Black-Americans may have a 40% higher incidence venous thromboembolism (VTE) incidence. However, whether other VTE characteristics and risk factors vary by race is uncertain. To compare demographic and baseline characteristics among White-and Black-Americans with VTE, we used data prospectively collected from consecutive consenting adults enrolled in seven Centers for Disease Control (CDC) Thrombosis and Hemostasis Centers from August 2003 to March 2009. These characteristics were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 49 publications
3
42
1
Order By: Relevance
“…Several studies have described a higher rate of VTE in blacks and some have investigated the association of SCT with thromboembolic disease [6][11], [16][18]. In support of the hypercoagulability hypothesis, Westerman noted increased levels of prothrombotic markers such as D-dimers, TAT (thrombin-antithrombin complexes) and the prothrombin cleavage fragment F1.2 in patients with SCT compared to HbAA controls [27].…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have described a higher rate of VTE in blacks and some have investigated the association of SCT with thromboembolic disease [6][11], [16][18]. In support of the hypercoagulability hypothesis, Westerman noted increased levels of prothrombotic markers such as D-dimers, TAT (thrombin-antithrombin complexes) and the prothrombin cleavage fragment F1.2 in patients with SCT compared to HbAA controls [27].…”
Section: Discussionmentioning
confidence: 95%
“…More research is needed related to racial/ethnic disparities in occurrence as well as causes and outcomes of VTE. Available information indicates that the prevalence of a number of hereditary conditions, such as factor V Leiden, that increases the risk of thrombosis, is lower among African Americans [22,23] . However, several other risk factors, such as hypertension and diabetes, have been found in higher rates among African-Americans with VTE compared to whites [11,22,23] .…”
Section: Issn 1927-6990 E-issn 1927-7008mentioning
confidence: 99%
“…[1315] Recently, racial differences have been elucidated in critical illness with African-Americans having a higher prevalence of sepsis compared to whites,[16] higher rates of cardiac arrest,[17, 18] noncardiogenic acute respiratory failure,[19] and venous thromboembolism. [20] Race not only affects disease prevalence but also clinical manifestations, severity, and mortality. [1214, 21] Although access to care has been the presumed default factor responsible for such disparities, recent evidence has shown that the relationship between race and disease is complicated with race modifying the disease through multiple mechanisms including genetic susceptibility, presence of comorbid conditions, socioeconomic status, and access to care.…”
Section: Introductionmentioning
confidence: 99%